Intraventricular hemorrhage after dural fistula embolization - Carvalho,Joana Chaves Gonçalves Rodrigues de (2017)
Abstract Background and objectives: Dural arteriovenous fistulas are anomalous shunts between dural arterial and venous channels whose nidus is located between the dural leaflets. For those circumstances when invasive treatment is mandatory, endovascular techniques have grown to become the mainstay of practice, choice attributable to their reported safety and effectiveness. We describe the unique and rare case of a dural arteriovenous fistula treated by transarterial embolization and complicated by an intraventricular hemorrhage. We aim to emphasize some central aspects of the perioperative management of these patients in order to help improving the future approach of similar cases. Case report: A 59-year-old woman with a previously diagnosed Cognard Type IV dural arteriovenous fistula presented for transarterial embolization, performed outside the operating room, under total intravenous anesthesia. The procedure underwent without complications and the intraoperative angiography revealed complete obliteration of the fistula. In the early postoperative period, the patient presented with clinical signs of raised intracranial pressure attributable to a later diagnosed intraventricular hemorrhage, which conditioned placement of a ventricular drain, admission to an intensive care unit, cerebral vasospasm and a prolonged hospital stay. Throughout the perioperative period, there were no changes in the cerebral brain oximetry. The patient was discharged without neurological sequelae. Conclusion: Intraventricular hemorrhage may be a serious complication after the endovascular treatment of dural arteriovenous fistula. A close postoperative surveillance and monitoring allow an early diagnosis and treatment which increases the odds for an improved outcome.